Dose Effects of Orally Administered Spirulina Suspension on Colonic Microbiota in Healthy Mice - Hu, Jinlu; Li, Yaguang; Pakpour, Sepideh; Wang, Sufang; Pan, Zhenhong; Liu, Junhong; Wei, Qingxia; She, Junjun; Cang, Huaixing; Zhang, Rui Xue (Frontiers in Cellular and Infection Microbiology, 2019)
Oral supplemented nutraceuticals derived from food sources are surmised to improve the human health through interaction with the gastrointestinal bacteria. However, the lack of fundamental quality control and authoritative consensus (e.g. formulation, route of administration, dose and dosage regimen) of these non-medical yet bioactive compounds are one of the main practical issues resulting in inconsistent individual responsiveness and confounded clinical outcomes of consuming nutraceuticals. Herein, we studied the dose effects of widely used food supplement, microalgae spirulina (Arthrospira platensis), on the colonic microbiota and physiological responses in healthy male Balb/c mice. Based on the analysis of 16s rDNA sequencing, compared to the saline-treated group, oral administration of spirulina once daily for 24 consecutive days altered the diversity, structure and composition of colonic microbial community at the genus level. More importantly, the abundance of microbial taxa was markedly differentiated at the low (1.5 g/kg) and high (3.0 g/kg) dose of spirulina, among which the relative abundance of Clostridium XIVa, Desulfovibrio, Eubacterium, Barnesiella, Bacteroides and Flavonifractor were modulated at various degrees. Evaluation of serum biomarkers in mice at the end of spirulina intervention showed reduced the oxidative stress and the blood lipid levels and increased the level of appetite controlling hormone leptin in a dose-response manner, which exhibited the significant correlation with differentially abundant microbiota taxa in the cecum. These findings provide direct evidences of dose-related modulation of gut microbiota and physiological states by spirulina, engendering its future mechanistic investigation of spirulina as potential sources of prebiotics for beneficial health effects via the interaction with gut microbiota.